Exploring Books as a Means of Strengthening Early Literacy Through a Play Approach in Early Childhood - Ayudya Rachmalia Putri; Salza Chusnul Khotimah (Journal of Art and Creativity in Early Childhood Education, 2025)
This study examines the use of Eksplore Book, a play-based learning medium designed to strengthen early childhood literacy skills through interactive activities such as guessing words, arranging letters, and recognizing objects. This research is motivated by the need for literacy media that is interesting, according to children's development, and easy to implement in the PAUD environment. Using a qualitative descriptive approach, this study observed the response of a five-year-old child during a directed learning session with Eksplore Book. Data were collected through direct observation and documentation of verbal expressions, written results, and children's involvement in activities. The results showed that children experienced improvements in letter recognition, word formation, and verbal expression, as well as showed high motivation and fun during the learning process. These activities not only support cognitive and fine motor development, but also encourage intrinsic motivation and spontaneous narrative abilities. These findings support the theory of early literacy and play-based learning, and demonstrate the effectiveness of media that combines exploratory and educational elements. In conclusion, the Eksplore Book is an effective and applicable medium in strengthening early literacy and has the potential to be applied more widely in the early childhood education environment.